Platelet Large Cell Ratio Levels in Smoking - Yılmaz, Mücahid; Kayançiçek, Hidayet; Gozel, Nevzat; Dağlı, Mustafa Necati; Eroğlu, Orkun; Çekici, Yusuf; Uku, Ökkeş (My University, 2018)
Objective: It was reported that smoking promotes endovascular thrombosis by increasing platelet adherence to endothelium and platelet aggregation. It is known that platelet volume indices (PVI) can indicate to increased platelet activity. Therefore, we aimed to evaluate effects of smoking on PVI values in healthy smokers.Materials and Methods: Two hundred and ninety eight consecutive current smoking, healthy male subjects and two hundred and six age-matched, non-smoking healthy male subjects were enrolled to the study. Complete blood count parameters (especially PVI values), and lipid profile were analyzed in all study participants and persons’ smoking habits were calculated as pack-years.Results: The study showed that platelet large cell ratio was (PLC-R) significantly higher by smokers compared to the non-smokers. PLC-R and PLCC (Platelet large cell count) values have a moderate degree of positive correlation with pack-year. In multivariate logistic regression analysis it was found that PLC-R levels were independent predictors of smoking (?=0.384, P: 0.03, 95% CI: 0.134 to 2.071). There were no statistically significant differences between two group in terms of other PVI parameters.Conclusion: Elevated PLC-R level is correlated with cigarette smoking positively and may be a useful indicator of coagulation activity in the smokers.
Keywords: Genel ve Dahili Tıp; Hematoloji